Rethinking Ginkgo biloba L.: Medicinal uses and conservation - Isah, Tasiu (Pharmacognosy Reviews)
Ginkgo biloba (G. biloba) is an ancient medicinal tree species that has been in existence for millennia without undergoing modifications due to its resistance to environmental stresses. Palaeobotanical history showed a wide distribution of the species across the globe but declined over geological time, becoming restricted to narrow geographical range with few surviving individuals in the modern day. The tree is slow growing, adapted to many ecological conditions and shows numerous adaptation in developmental patterns. Medicinal use of the species is attracting research interest, especially the various parts of the tree that are used in orthodox or traditional medicine to treat diseases due to the many bioactive compounds. The primary compounds receiving increasing research interest are the triterpene lactones and flavonoids; these are the target of biotechnological strategies being employed to enhance production. Many genetic and environmental factors have contributed to the endangered status of the species; conservation measures are required to protect it from extinction. In many countries, the cultivation of plantations for the supply of ginkgo leaf‑based pharmaceutical formulations is in progress, and efforts to standardize ginkgo leaf extract as herbal medication for human use are being made. Microcuttings and cuttings, cryopreservation, and plant tissue culture have all aided to conserve G. biloba.
Keywords: Bilobalides; conservation; Ginkgo biloba; ginkgolides; short shoots; triterpene lactones